Divergent brain solute clearance in rat models of cerebral amyloid angiopathy and Alzheimer’s disease - Sunil Koundal; Xinan Chen; Zachary Gursky; Hedok Lee; Kaiming Xu; Feng Liang; Zhongcong Xie; Feng Xu; Hung-Mo Lin; William E. Van Nostrand; Xianfeng Gu; Rena Elkin; et al. (iScience)
Summary: Brain waste clearance from the interstitial fluid environment is challenging to measure, which has contributed to controversy regarding the significance of glymphatic transport impairment for neurodegenerative processes. Dynamic contrast enhanced MRI (DCE-MRI) with cerebrospinal fluid administration of Gd-tagged tracers is often used to assess glymphatic system function. We previously quantified glymphatic transport from DCE-MRI data utilizing regularized optimal mass transport (rOMT) analysis, however, information specific to glymphatic clearance was not directly derived. To fill this knowledge gap, we here implemented unbalanced rOMT analysis which allows for assessment of both influx and clearance. Dynamic influx/clearance brain maps were derived from rTg-DI rats with cerebral amyloid angiopathy (CAA) and TgSD-AD rats with Alzheimer’s disease (AD). The rTg-DI rats with severe CAA disease exhibited abnormal influx/clearance kinetics, while TgSD-AD rats with a moderate Aβ plaque load exhibited normal transport suggesting that different Aβ lesions and their overall burden differentially impact glymphatic system function.